On the Self-Similar Solution of The Problem of Unsteady Movement of Groundwater Near a Reservoir in the Presence of Nonlinear Evaporation (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The problem of filtration near new channels and reservoirs, taking into account evaporation, is investigated. For one case of the dependence of evaporation on time, a self-similar solution of the problem with an unknown boundary has been found, which makes it possible to draw certain qualitative conclusions and which can be used as a test.